2018
DOI: 10.1039/c7cc08178b
|View full text |Cite
|
Sign up to set email alerts
|

Thiomolybdate [Mo3S13]2−nanocluster: a molecular mimic of MoS2active sites for highly efficient photocatalytic hydrogen evolution

Abstract: Thiomolybdate [MoS] nanoclusters, as a molecular mimic of MoS edge sites, showed high efficiency in catalyzing photochemical H evolution from a molecular system of Ru(bpy)Cl-ascorbic acid (HA) under visible light irradiation (≥420 nm), providing a turnover number of 1570 and an initial turnover frequency of 335 h for H evolution based on the [MoS] catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 30 publications
1
43
0
Order By: Relevance
“…Such low activities are consistent with previous reports for perovskite‐based photocatalysis without help of stabilizer and cocatalyst . [Mo 3 S 13 ] 2 2− nanoclusters as the cocatalyst have an excellent hydrogen evolution activity and stability in acid condition . The XRD of Mo 3 S 13 2− treated by HBr solution was shown in Figure S7.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Such low activities are consistent with previous reports for perovskite‐based photocatalysis without help of stabilizer and cocatalyst . [Mo 3 S 13 ] 2 2− nanoclusters as the cocatalyst have an excellent hydrogen evolution activity and stability in acid condition . The XRD of Mo 3 S 13 2− treated by HBr solution was shown in Figure S7.…”
Section: Resultssupporting
confidence: 91%
“…[7][8][9] [Mo 3 S 13 ] 2 2− nanoclusters as the cocatalyst have an excellent hydrogen evolution activity and stability in acid condition. [24][25][26] The XRD of Mo 3 S 13 2− treated by HBr solution was shown in Figure S7. The crystal structure can be assigned as a standard (NH 4 ) 2 Mo 3 S 13 ÁnH 2 O XRD data (JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…12 Recently, homogeneous photocatalytic HER activity of thiomolybdate [Mo 3 S 13 ] 2– was reported. 13 In a subsequent study, it was shown that under catalytic conditions, terminal disulfide ligands exchange with solvent (H 2 O) over time and influence the catalytic activity. 14 In particular, partial exchange of terminal disulfides (S 2 2– ) with aqua ligands leads to [Mo 3 S (13- x ) (H 2 O) x ] ( x -2)+ ( x = 2, 4) which could be identified as the most active catalytic species in solution.…”
Section: Introductionmentioning
confidence: 99%
“…XPS was used to analyze the chemical bonds on the surface of those samples, as shown in Supplementary Figure S1 and (Quinlan et al, 2016;Li et al, 2018b;Ni et al, 2018;Song et al, 2019;Yue et al, 2019;Han et al, 2020), respectively. The Mo 3 d and S 2s highly deconvoluted spectra of F-MoS 2 @NC-0.8 (Figure 3B) showed the three fitted peaks at 235.7, 232.5 and 229.4 eV are related to Mo 6+ −O, Mo 3d 3/2 and Mo 3d 5/2 (Feng et al, 2015;Ahn et al, 2018;Lei et al, 2018). It should be noted that the slight surface oxidation of MoS 2 could cause the existence of Mo 6+ −O.…”
Section: Resultsmentioning
confidence: 97%